Unstressed PACVD diamond films on steel pre-coated with a composite multilayer - F. J. G. Silva (2005)
Although the direct deposition of CVD diamond coatings on ferrous substrates is highly desirable, many technological problems hinder the production of commercial applications, mainly due to a lack of adhesion. Diamond can be grown on such substrates; however, film detachment cannot usually be avoided. Suitable buffer layers are the most commonly used solution to overcome adhesion problems. In the present work, we report CVD diamond deposition on steel substrates pre-coated with a multilayer composed of Ni/Cu with embedded diamond particles. With this interlayer a range of diamond film growth parameters were found to give crack-free and nearly strain-free diamond continuous coatings. Film morphology and quality are assessed by scanning electron microscopy (SEM), profilometry, and micro-Raman spectroscopy. The adhesion of the films is strong enough to with stand micro-abrasion tests. (C) 2004 Elsevier B.V All rights reserved.